An Ai Chi-based aquatic group improves balance and reduces falls in community-dwelling adults: A pilot observational cohort study. (16th November 2016) - Skinner, Elizabeth H.; Dinh, Tammy; Hewitt, Melissa; Piper, Ross; Thwaites, Claire
ABSTRACT: Background : Falls are associated with morbidity, loss of independence, and mortality. While land-based group exercise and Tai Chi programs reduce the risk of falls, aquatic therapy may allow patients to complete balance exercises with less pain and fear of falling; however, limited data exist. Objective : The objective of the study was to pilot the implementation of an aquatic group based on Ai Chi principles (Aquabalance) and to evaluate the safety, intervention acceptability, and intervention effect sizes. Design : Pilot observational cohort study. Methods : Forty-two outpatients underwent a single 45-minute weekly group aquatic Ai Chi-based session for eight weeks (Aquabalance). Safety was monitored using organizational reporting systems. Patient attendance, satisfaction, and self-reported falls were also recorded. Balance measures included the Timed Up and Go (TUG) test, the Four Square Step Test (FSST), and the unilateral Step Tests. Results : Forty-two patients completed the program. It was feasible to deliver Aquabalance, as evidenced by the median (IQR) attendance rate of 8.0 (7.8, 8.0) out of 8. No adverse events occurred and participants reported high satisfaction levels. Improvements were noted on the TUG, 10-meter walk test, the Functional Reach Test, the FSST, and the unilateral step tests ( p < 0.05). The proportion of patients defined as high falls risk reduced from 38% to 21%. The study was limited by its small sample size, single-center nature, and the absence of a control group. Conclusions : Aquabalance was safe, well-attended, and acceptable to participants. A randomized controlled assessor-blinded trial is required.